Three versions of orphanhood in César Vallejo's poetry - Rodríguez Zapata, Irma Aniela (2019)
In the vast poetic work of César Vallejo it's possible to identify then absence and nostalgia of past time as thematic records with some frequency. This article studies the concept of orphanhood through three variations of the helplessness presented in Vallejo's poetry. To do this we examine here events such as the inhibited space, the mother's figure, and the lost paradises in order to investigate and contrast the many manifestations of orphanhood in Vallejo's universe Key Words: orphanhood, absence, César Vallejo, poetry, lost paradises, inhabited space.